Intravenous thrombolytic therapy for cerebral infarction due to the Persheron artery occlusion. Case report - Sargylana A. Chugunova; Mikhail M. Popov; Anastasia E. Makievskaya; Natalia V. Yakovleva; Varvara V. Tarabukina (ZAO "Consilium Medicum", 2021)
Occlusion of the artery of Percheron is the cause of bilateral thalamic infarctions, sometimes involving structures of the midbrain. A clinical case of intravenous thrombolytic therapy for ischemic stroke due to the occlusion of the Percheron artery in a 72-year-old female patient who developed depression of consciousness, oculomotor disorders, dysarthria, ataxia, pyramidal disorders, and cognitive disorders is presented. Magnetic resonance imaging, which detected bilateral thalamus paramedian infarction in the acute stage, made it possible to diagnose the occlusion of the Percheron artery. Intravenous thrombolysis led to a rapid regression of symptoms; at the end of the acute period of the disease, the patient was discharged from the hospital with a slight neurological deficit and with a good functional outcome. After a one year the dynamic observation revealed persistent mild cognitive disorders; magnetic resonance imaging showed small symmetric cystic-gliosis changes in the medial parts of the thalamus on both sides. Timely diagnosis and intravenous thrombolytic therapy contribute to a good outcome of cerebral infarction due to the Percheron's artery occlusion.